PROSES PEMULIHAN INTERAKSI SOSIAL SISWA TERISOLIR MELALUI KONSELING INDIVIDU: STUDI FENOMENOLOGIS - Nengsi; Nurlaila Syipa Unnupus; Hanin Ulya; Baiq Mahyatun; Hesya Fadila Imtiyaz; Rini Sugiartini; Anisa Sapira; Imam Nawawi Zain; Denda Wanda Ariani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social isolation is a social developmental problem characterized by students' limited involvement in social interactions and low acceptance by their peers. This condition may hinder students' psychosocial development, self-confidence, and social adjustment. This study aimed to explore the lived experiences of socially isolated students during the process of recovering their social interactions after participating in individual counseling services. This study employed a qualitative approach using a transcendental phenomenological design. The research was conducted in Class X.6 of SMAN 1 Sikur, involving 38 students, from whom four participants were purposively selected based on sociometric assessment results. Data were collected through sociometry, in-depth interviews, observations, and documentation, and were analyzed using Moustakas' transcendental phenomenological procedures, including epoche, horizontalization, clustering of meanings, textural description, structural description, and synthesis of meanings and essences. The findings revealed five major themes: (1) experiences of alienation and loneliness, (2) fear of social rejection, (3) individual counseling as a space for self-reflection and self-acceptance, (4) the emergence of courage to reinitiate social interactions, and (5) the reestablishment of meaningful social relationships. The findings indicate that the recovery process occurred gradually through changes in self-perception, increased self-confidence, and greater willingness to build relationships with peers. This study concludes that sociometry is an effective instrument for the early identification of socially isolated students, while individual counseling plays a significant role in facilitating the recovery of students' social interactions within the school environment.